Fintech Lending: Analysis of the Response and Existence of Peer To Peer Lending Growth in Indonesia - Nopiah, Ririn (PT Inovasi Pratama Internasional, 2025)
The development of Financial Technology / Fintech, namely peer-to-peer (P2P) lending in Indonesia has experienced rapid growth. This study aims to identify the response and existence of Fintech lending and analyze the determinants that have the potential to differentiate the response of Fintech growth in Indonesia during a certain period. The analysis method uses several stages, namely Klassen typology analysis and multiple linear regression model analysis. The research data comes from quantitative data on Fintech Lending in Indonesia which is officially registered with the Financial Services Authority (OJK) from 2021 to 2023. The variables used include P2P Lending loan volume, investor fund volume, default rate, accessibility, interest rates, and inflation on the growth of Fintech-lending transactions. The results show that loan volume, investor fund volume and default rate have an influence on the growth of Fintech-lending in Indonesia. In addition, DKI-Jakarta is an area in quadrant III (vulnerable and risky), while Gorontalo is an area with the potential to develop in quadrant IV. The regions that are in the growing but risky criteria are Banten, West Java, Central Java, D.I.Yogyakarta, East Java, NTB, Central Sulawesi, South Sulawesi, and West Sumatra. This study provides important insights into the dynamics of Fintech-lending growth in Indonesia and becomes an analysis of policy considerations to support the development of a healthy and sustainable fintech-lending sector. These findings are relevant for policymakers, industry practitioners, and researchers interested in inclusive finance and financial innovation in developing countries.